Fenomena Joki Pelatihan Prakerja di Tanjungpinang - Febi Putri Tampubolon; Emmy Solina; Marisa Elsera (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
This study aims to find out how from the active actors of Pre-employment training jockeys and how the perpetrators decided to become an active actor in pre-employment training jockey activities in Tanjungpinang. This study uses a qualitative research method with a descriptive approach. Data collection techniques in study used semi-structured interviews, observations online and offline. The sampling technique used is snowball sampling with 8 informants as jockey service providers, 2 informants as jockey service recipients, and 1 informant as Head of the Placement and Training of Manpower, Department of Manpower, Cooperatives, SMes, Tanjungpinang. Based on the findings the researcher, researcher found that there were jockeys in the Pre-employment training program in Tanjungpinang, especially in 2020 to 2021. The findings of this the study illustrates that most of the informants are interested in Pre-employment program incentives as a survival strategy during pandemic covid-19, some informants decided to become part of jockeys for non-material interests, including achieving good relations with neighbors, and the sense of satisfaction felt when one of the family members passed to participate in the Pre-employment Program.